The Influence of the Teams Games Tournament (TGT) Type Cooperative Learning Model on the Mathematical Understanding Ability and Mathematical Attitude of Students - Siti Ningsih; Fahmi Halim; Mohammad Ridho’i; Dwi Kharisma; Dwi Melati (EDUJAVARE: International Journal of Educational Research, 2026)
Mathematical comprehension skills and mathematical attitudes are two important aspects of mathematics learning; however, observations at MTs Wahid Hasyim Sukosari Kunir indicate that both aspects remain relatively low as a result of teaching that tends to be teacher-centered. The purpose of this study is to ascertain how students' mathematics attitudes and understanding abilities are affected by the Teams Games Tournament (TGT) cooperative learning approach. This study used a quantitative methodology with a quasi-experimental design more precisely, a Nonequivalent Pretest-Posttest Control Group Design. The study population consisted of 41 seventh-grade students, all of whom were included in the sample through saturation sampling, comprising 21 students in the experimental class and 20 students in the control class. Data were collected using a mathematical comprehension test and a mathematical attitude questionnaire that met validity and reliability criteria, and were then analyzed using descriptive statistics, normality tests, homogeneity tests, and an independent samples t-test. With a significance value (Sig. 2-tailed) of 0.000 < 0.05 for both variables, the study's findings show that the Teams Games Tournament (TGT) cooperative learning model significantly affects students' mathematical attitudes and comprehension. As a result, the Teams Games Tournament (TGT) cooperative learning model works well as an alternate teaching strategy for raising students' mathematical attitudes and comprehension.